Analisis Kesulitan Belajar Siswa: Pendekatan Tes Diagnostik Berganda Dua Tingkat dan Kuesioner: (Analysis of Student Learning Difficulties: Two-Tier Multiple-Choice Diagnostic Test and A Questionnaire Approach) - Situmorang, Jesika; Hasairin, Ashar (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2025)
Learning is a process of interaction between teachers and students that aims to achieve maximum results, but is often hampered by learning difficulties, both from internal factors such as psychology, interests, and intelligence of students, as well as external factors such as family and community environment. Initial studies at SMA St. Ignatius Medan showed that the virus material in biology lessons was one of the most difficult materials, due to its abstract nature, the use of Latin terms, and limited laboratory practice. The low cognitive achievement of students in the aspects of understanding, applying, and assessing the material indicates the need for special attention. The study aims to identify learning difficulties based on students' understanding of virus material in Class X Science at St. Ignatius Senior High School Medan, as well as the main causal factors. The research method employed is descriptive quantitative. The population includes all science classes at St. Ignatius Senior High School Medan, with the sample selected using a total sampling technique. Data collection was conducted using a two-tier multiple-choice diagnostic test and a questionnaire. The results of the study indicated that students experienced learning difficulties, with the highest rate of misconceptions occurring on the indicators of analyzing the characteristics of viruses, compiling a list of proposed preventive measures to minimize the impact of viral infections, and classifying viruses based on their genetic material along with examples. The highest rate of lack of understanding was observed on the indicators of comparing the lytic and lysogenic cycles in viral reproduction, explaining the role of viruses in life, and classifying viruses based on their genetic material along with examples. The main factors contributing to students' learning difficulties include factors related to facilities and infrastructure, particularly in the aspect of practical activities, and the intrinsic nature of virus material, especially its use of latin terminology. Abstrak. Pembelajaran merupakan proses interaksi antara guru dan siswa yang bertujuan mencapai hasil maksimal, namun sering terhambat oleh kesulitan belajar, baik yang berasal dari faktor internal seperti psikologis, minat, dan intelegensi siswa, maupun faktor eksternal seperti lingkungan keluarga dan masyarakat. Studi awal di SMA St. Ignatius Medan menunjukkan bahwa materi virus dalam pelajaran biologi menjadi salah satu materi tersulit, karena sifatnya yang abstrak, penggunaan istilah Latin, dan keterbatasan praktik laboratorium. Rendahnya capaian kognitif siswa dalam aspek memahami, menerapkan, hingga menilai materi tersebut menunjukkan perlunya perhatian khusus. Penelitian bertujuan untuk mengetahui kesulitan belajar berdasarkan pemahaman peserta didik pada materi virus kelas X IPA SMA St. Ignatius Medan dan faktor- faktor penyebab utamanya. Metode penelitian deskriptif kuantitatif. Populasi seluruh kelas IPA yang ada di SMA St. Ignatius Medan. Sampel diambil dengan teknik total sampling. Teknik pengumpulan data adalah instrumen tes diagnostik berganda dua tingkat (two-tier multiple choice) dan angket. Hasil penelitian menunjukkan bahwa siswa mengalami kesulitan belajar kategori miskonsepsi tertinggi pada indikator menganalisis ciri-ciri virus, indikator membuat daftar usulan tindakan preventif untuk meminimalkan dampak infeksi virus, dan indikator mengelompokkan virus berdasarkan substansi genetiknya beserta contohnya, serta tidak paham tertinggi pada indikator membandingkan siklus litik dengan lisogenik pada reproduksi virus, indikator menjelaskan peranan virus dalam kehidupan, dan indikator mengelompokkan virus berdasarkan substansi genetiknya beserta contohnya. Faktor faktor utama penyebab kesulitan belajar siswa terdiri dari faktor sarana dan prasarana pada aspek kegiatan praktikum serta faktor sifat dari materi virus pada aspek bahasa latin.